2009
DOI: 10.1139/z09-010
|View full text |Cite
|
Sign up to set email alerts
|

Ambient temperature is more important than food availability in explaining reproductive timing of the bat Sturnira lilium (Mammalia: Chiroptera) in a montane Atlantic Forest

Abstract: Reproduction of bats is determined by a suite of endogenous and exogenous factors. Among exogenous influences, special attention has been given to the influence of food availability. However, in highland forests, severe decreases in temperature during the cold and dry season may also play an important role. In the present study we tested the influence of ambient temperature and food availability on the timing of reproduction in the frugivorous bat Sturnira lilium (E. Geoffroy, 1810). We conducted a 15-month mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 26 publications
2
32
1
10
Order By: Relevance
“…Some authors say that testes location is not a good indicator of male reproductive activity, since the spermatic activity is continuous (Fabián and Marques, 1989;Moraes, 2008). Other authors suggest the use of other external indicators of active reproduction, such as behavior, glands, and odors Mello et al, 2009). However, in the present study, the higher proportion of males with scrotal testes was synchronized with the proportion of potentially receptive females (lactating and post-lactating), indicating that the more females are in estrus, the more males will show maximum sperm production.…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…Some authors say that testes location is not a good indicator of male reproductive activity, since the spermatic activity is continuous (Fabián and Marques, 1989;Moraes, 2008). Other authors suggest the use of other external indicators of active reproduction, such as behavior, glands, and odors Mello et al, 2009). However, in the present study, the higher proportion of males with scrotal testes was synchronized with the proportion of potentially receptive females (lactating and post-lactating), indicating that the more females are in estrus, the more males will show maximum sperm production.…”
Section: Discussioncontrasting
confidence: 74%
“…Mello et al (2009) observed that, although S. lilium did not have its reproduction synchronized with rainfall nor fruit availability, births occurred in the rainy season. These authors suggest that temperature has the strongest influence on the reproduction of S. lilium in montane forests.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations